The Effectiveness of Implementing Government Accounting Standard No. 71 of 2010 on the Quality of Financial Statements at the Department of Communication and Informatics of Tebing Tinggi - Lasmian Panjaitan; Hendra Saputra (Cattleya Darmaya Fortuna, 2026)
This study aims to analyze the effectiveness of implementing Government Regulation (PP) No. 71 of 2010 regarding Accrual-Based Government Accounting Standards (SAP) on the quality of financial statements at the Department of Communication and Informatics (Diskominfo) of Tebing Tinggi.The research employs a descriptive qualitative method with a case study approach. The findings indicate that the effectiveness of SAP implementation is influenced by the proficiency of human resources, system readiness, and leadership commitment. The quality of financial statements is measured through four qualitative characteristics: relevance, reliability, comparability, and understandability. Recommendations are provided to enhance compliance and the utility of financial information.